RESPIRATORY MUSCLE IMPAIRMENT EVALUATED WITH MEP/MIP RATIO IN CHILDREN AND ADOLESCENTS WITH CHRONIC RESPIRATORY DISEASE - Iván Rodríguez-Núñez; Gerardo Torres; Soledad Luarte-Martinez; Carlos Manterola; Daniel Zenteno (Sociedade de Pediatria de São Paulo, 2020)
ABSTRACT Objective: To evaluate the strength of respiratory muscles and to compare maximum inspiratory (MIP) and expiratory (MEP) pressure and MEP/MIP ratio between patients with chronic respiratory diseases and healthy individuals. Methods: Case-control study. Individuals with neuromuscular disease and post-infectious bronchiolitis obliterans were considered. In addition, they were also matched according to anthropometric and demographic characteristics with healthy children and adolescents. MIP, MEP in the three groups, and pulmonary function only in patients with chronic respiratory diseases were recorded. Results: A total of 52 subjects with CRD (25 with neuromuscular disease, and 27 with post-infectious bronchiolitis obliterans) and 85 healthy individuals were included, with an average age of 11.3±2.1 years. Patients with neuromuscular disease and post-infectious bronchiolitis obliterans presented lower MIP and MEP when compared with healthy individuals, although MEP/MIP ratio was lower in patients with neuromuscular disease (0.87±0.3) and higher in patients with post-infectious bronchiolitis obliterans (1.1±0.3) compared to the healthy group (0.97±0.2). Only in patients with neuromuscular disease a negative correlation was observed between MEP/MIP ratio and age (r=-0.50; p=0.01). Conclusions: Differences in the pattern of muscular weakness between patients with chronic respiratory diseases were observed. In patients with neuromuscular disease, a decrease in the MEP/MIP ratio depending on MIP was verified; and in those patients with post-infectious bronchiolitis obliterans, an increase in the MEP/MIP ratio depending on MIP was also observed.